Laser assisted glass frit sealing for production large area DSCs panels. (October 2016) - Ivanou, D.K.; Santos, R.; Maçaira, J.; Andrade, L.; Mendes, A.
Highlights: Laser assisted sealing of lead-free glass frit was used for production of DSC panel. The panel comprises 90 individual DSCs cells sealed with glass. Both indoor and outdoor aging tests showed good stability of panel efficiency. Sealed cells remained stable during continuous operation at outdoor conditions. Abstract: For the first time laser assisted sealing using lead-free glass frit was successfully applied for producing a DSC panel with a total sealed area of 1638 cm 2 and active area of 990 cm 2 . The panel comprises 90 DSCs individual glass sealed cells (140 mm × 13 mm) arranged in 10 sub-modules (150 mm × 150 mm). Indoor aging of individual sub-modules in dark and at ambient temperature for 100 days showed rather small decrease of the photocurrent conversion efficiency: −1.23 · 10 −4  day −1 . The DSC panel was tested under outdoor working conditions during 47 days in summer time (Porto, Portugal), where the average day illumination level was about 6 kW h m −2 . After 47 days of continuous power production the assembled panel kept 86% of the initial efficiency. No leakage of electrolyte or visual defects in the sealed glass frit were detected. Glass sealed DSCs performed superior stability under 1000 h of ageing in a climatic chamber when compared to polymer sealed cells. The results show that the laser assisted sealing can be applied to large area DSC modules.